Inhibition of miR-497 improves functional outcome after ischemic stroke by enhancing neuronal autophagy in young and aged rats. (July 2019) - Chen, Xudong; Lin, Siyang; Gu, Lei; Zhu, Xiaohong; Zhang, Yinuo; Zhang, Hongxia; Shao, Bei; Zhuge, Qichuan; Jin, Kunlin
Abstract: Over the years miR-497 has been found to play a vital role in the pathogenesis of neurological diseases, including ischemic stroke. However, its underlying mechanism remains largely unexplored. Here, we used miR-497 agomir (miR-497 agonist), miR-497 antagomir (miR-497 inhibitor) and 3-MA (autophagy inhibitor) to treat ischemic rats (n = 10–12 per group) induced by permanent distal middle cerebral artery occlusion (dMCAO), followed the functional outcome assessment 24 h after dMCAO. We found that treatment of miR-497 antagomir, but not miR-497 angomir, reduced the infarct volume and improved neurological deficits after ischemic stroke, along with upregulation of the autophagy-related protein LC3 expression (mean ± SEM, p < 0.05). While the ischemic rats treated with 3-MA exhibited inhibition of autophagy, which in turn abolished functional recovery as observed in miR-497 antagomir-treated group (p < 0.05). Interestingly, the role of miR-497 in functional recovery in aged ischemic rats was less effective, compared to young adult ischemic rats (p < 0.05). Our data suggest that inhibition of miR-497 could protect cerebral ischemic injury by enhancing autophagy and also age-dependent. Highlights: The first study showing miR-479 improved functional outcome after ischemia by enhancing autophagy. Neuronal autophagy is beneficial for stroke in the early stage, and probably is a major part of survival mechanism of acute cerebral ischemia. MiR-497 affected on mitochondrion-targeted Bcl-2 and may directly act on LC3. MiR-497 inhibition-mediated neuroprotection is age-dependent, which is less effective in aged rats.